PENGARUH SOFT SKILL DAN PERENCANAAN KARIR TERHADAP KINERJA KARYAWAN DENGAN KUALITAS PELATIHAN SEBAGAI VARIABEL MODERTOR (Studi empiris pada PT. Krakatau Tirta Industri Cilegon) - Rokhayati, Ana; Kambara, Roni; Ibrahim, Mahdani (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2017)
In the world of work the importance of soft skills (soft competency), career planning is needed in improving employee performance and the influence of quality training in improving soft skills, career planning and employee performance. This study aims to determine the effect of soft skills and career planning on employee performance with the quality of training as a moderating variable. Indentent variable in this research is soft skill and career planning, moderating variable is training quality and dependent variable is employee performance. This research was conducted at PT. Krakatau Tirta Industri Cilegon. In this study the sample is taken as many as 105 employees from a total of 142 employees of PT. Krakatau Tirta Industri Cilegon with proportionate random sampling technique and primary data were collected by using quesioner in the form of statement list and analyzed using Structural Equation Modeling (SEM) with the help of Smart Partial Least Square (PLS) statistical software. The results showed that soft skill had positive and significant effect on employee performance, career planning had positive and significant effect on employee performance and quality of training had positive and significant effect to employee performance. While the quality of training is not proven to have a positive and significant impact on soft skills, neither does the quality of training have a positive and significant impact on career planning.